A conceptual framework for how structural changes in emerging acute substance use service models can reduce stigma of medications for opioid use disorder - Becker, Timothy D.; Eschliman, Evan L.; Thakrar, Ashish P.; Yang, Lawrence H. (Frontiers in Psychiatry, 2023)
Stigma toward people taking medication for opioid use disorder (MOUD) is prevalent, harmful to the health and well-being of this population, and impedes MOUD treatment resource provision, help-seeking, and engagement in care. In recent years, clinicians have implemented new models of MOUD-based treatment in parts of the United States that integrate buprenorphine initiation into emergency departments and other acute general medical settings, with post-discharge linkage to office-based treatment. These service models increase access to MOUD and they have potential to mitigate stigma toward opioid use and MOUD. However, the empirical literature connecting these emerging service delivery models to stigma outcomes remains underdeveloped. This paper aims to bridge the stigma and health service literatures via a conceptual model delineating how elements of emerging MOUD service models can reduce stigma and increase behavior in pursuit of life goals. Specifically, we outline how new approaches to three key processes can counter structural, public, and self-stigma for this population: (1) community outreach with peer-to-peer influence, (2) clinical evaluation and induction of MOUD in acute care settings, and (3) transition to outpatient maintenance care and early recovery. Emerging service models that target these three processes can, in turn, foster patient empowerment and pursuit of life goals. There is great potential to increase the well-being of people who use opioids by reducing stigma against MOUD via these structural changes.